DEVELOPING TEACHERS DIGITAL LITERACY COMPETENCIES THROUGH HYBRID LEARNING - Edwina , Tirzsatyara (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
Developments in the field of education are one of the factors in the progress of learning. The development of science and information technology in 21st century learning requires digital era competencies and skills for professional teachers. Digital competencies must be possessed by teachers including mastery of information, communication, educational content creation, security, and educational problem solving. Teacher creativity in supporting digital competencies is by developing more dynamic learning models and methods, one of which uses hybrid learning methods. Teachers' digital competence and pedagogical competence in utilizing innovative learning methods still have gaps. This research aims to examine the development of teachers' digital literacy competencies through hybrid learning. The method used in this research is descriptive with a qualitative approach. The data obtained is using secondary data which is study literature. Based on the research results, teachers' digital competencies have not been implemented optimally, but can be improved through the use of hybrid learning methods by maximizing learning strategies and learning success indicators. Keywords: Teachers Development, Digital Literacy Competencies, Hybrid Learning